A high BMI is a risk factor in younger patients with de novo acute myelogenous leukemia. (17th September 2015) - Crysandt, Martina; Kramer, Michael; Ehninger, Gerhard; Bornhäuser, Martin; Berdel, Wolfgang E.; Serve, Hubert; Röllig, Christoph; Kaifie, Andrea; Jost, Edgar; Brummendorf, Tim H.; Wilop, Stefan
Abstract: Overweight and obese patients have an increased risk to develop several malignancies and, additionally, body mass index (BMI) impacts on outcome in several solid tumors. However, little is known for AML. We analyzed a cohort of 3526 patients with AML treated in three prospective multicenter trials within the German Study Alliance Leukemia. In multivariate analyses, we identified BMI as an independent risk factor for both DFS (HR 1.014, P  = 0.0217) and OS (HR 1.015, P  < 0.0036). Interestingly, overweight and obesity seemed to be a risk factor predominantly in patients with de novo AML younger than 65 yr with intermediate risk and adverse cytogenetics. Overweight with a BMI ≥25 kg/m² best discriminated the worse outcome and led to an absolute reduction in long‐term survival of 5–7% in the group of all younger patients (3‐yr OS 39.9% vs. 47.3%; 10‐yr OS 28.7% vs. 33.8%, P  = 0.0002). Additionally, response to induction therapy was significantly reduced in these patients (76.9% vs. 82.8%, P  < 0.0001). Thus, in younger patients with de novo AML, overweight and obesity are risk factors for impaired response to induction therapy, DFS and OS. This effect is, in part but not fully, explained by dose reduction such as dose‐capping at a body surface area of 2 m².